Rancang Bangun Sistem Pemberian Pakan Ikan Lele Otomatis Berbasis Mikrokontroler - Hanifiyah Darna Fidya Amaral; Divac Nabiel Akbar; Afidah Zuroida (Politeknik Negeri Malang, 2022)
Technology allows the process of managing catfish remotely, namely catfish managers do not need to manage feeding. In addition, the automated system makes it possible to preserve the quality of catfish as well as savings in feed costs. Today's automated tools mostly use a microcontroller as a controller. Microcontrollers can be programmed to execute commands as needed and at the same time become a form of automation system application in catfish management. In this study, the author designed a microcontroller-based automatic catfish feeding system. The microcontroller used is the ATMega 28 microcontroller which is connected to the RTC DS3231 module. This microcontroller is also equipped with a servo motor that works to move the fish feed valve automatically. The servo motor used is the MG996R servo which has a working voltage of 6V which is sourced from the power supply which is lowered in voltage using step down. The RTC DS3231 module is connected with the arduino uno R3 module, which is the control center of the automatic feed device. The microcontroller turns on following the fish feeding time, which is 8 am and 3 pm. The servo motor will work to open the valve twice in one day automatically with an angle or percentage of the feed valve opening by 35% - 45% for approximately 5 - 10 seconds and the feed that comes out is about 40-70 grams per 10 seconds.